An Improved High Yield Total Synthesis and Cytotoxicity Study of the Marine Alkaloid Neoamphimedine: An ATP-Competitive Inhibitor of Topoisomerase IIα and Potent Anticancer Agent - Li, Linfeng (MDPI, 2014)
Recently, we characterized neoamphimedine (neo) as an ATP-competitive inhibitor of the ATPase domain of human Topoisomerase IIα. Thus far, neo is the only pyridoacridine with this mechanism of action. One limiting factor in the development of neo as a therapeutic agent has been access to sufficient amounts of material for biological testing. Although there are two reported syntheses of neo, both require 12 steps with low overall yields (≤6%). In this article, we report an improved total synthesis of neo achieved in 10 steps with a 25% overall yield. In addition, we report an expanded cytotoxicity study using a panel of human cancer cell lines, including: breast, colorectal, lung, and leukemia. Neo displays potent cytotoxicity (nM IC(50) values) in all, with significant potency against colorectal cancer (lowest IC(50) = 6 nM). We show that neo is cytotoxic not cytostatic, and that neo exerts cytotoxicity by inducing G2-M cell cycle arrest and apoptosis.